Nutrition in Indonesia toddlers and preschools: understanding challenges and strategies - Saptawati Bardosono (World Nutrition Journal, 2022)
There is surely rapid development of toddler and preschool age children, especially related to human brain development. Poor development among under-five children in Indonesia in 2010 is ranged 40–59%. Global data shows that there is triple burden of malnutrition, and amongst improper behavior, the two highest clinical symptoms are hyperactivity and showing anger when displeased. This shows that children need nurturing care in which has its contribution through the life course.